2008
DOI: 10.1097/wnr.0b013e328312181c
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent changes in striatal xCT protein expression in hemi-Parkinson rats

Abstract: Altered glutamate signaling is associated with Parkinson's disease. To study the involvement of the cystine/glutamate antiporter in the pathogenesis of Parkinson's disease, we developed new polyclonal antibodies recognizing xCT, the specific subunit of this antiporter. The striatal xCT protein expression level was investigated in a hemi-Parkinson rat model, using semiquantitative western blotting. We observed time-dependent changes after a unilateral 6-hydroxydopamine lesion of the nigrostriatal pathway with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…The expression of xCT in the brain was confirmed in the protein level by Western blotting and immunohistochemistry (30,176,250). Especially high levels were found in the meninges (250).…”
Section: Expression Of System X Cmentioning
confidence: 80%
See 1 more Smart Citation
“…The expression of xCT in the brain was confirmed in the protein level by Western blotting and immunohistochemistry (30,176,250). Especially high levels were found in the meninges (250).…”
Section: Expression Of System X Cmentioning
confidence: 80%
“…In the cortex of aged APP23 mice, xCT overexpression is accompanied by reduced glutamate uptake and increased extracellular glutamate levels (238). With regard to models of PD, an ipsilateral increase in striatal xCT protein levels occurred in 6-hydroxydopamine (6-OHDA)-lesioned hemi-Parkinson rats 3 weeks after an injection (176). Although the functional significance was not determined in the former study, follow-up studies using xCT -/ -mice showed that dopaminergic neurons in the substantia nigra of system x c --deficient mice were highly protected against 6-OHDA-induced neurodegeneration (175).…”
Section: Synopsis and Future Directions For System X Cmentioning
confidence: 99%
“…It is noteworthy that mitochondrial dysfunction, oxidative stress, and ultimate nigrostriatal toxicity may be due, in part, to diminished glutathione levels (Penugonda et al, 2005). Not surprisingly, the depletion in glutathione is linked to an increase in xCT protein, at least in rats receiving unilateral 6-hydroxydopamine lesions (Massie et al, 2008). In general, a neuroprotective role has been clearly established for glutathione and N-acetylcysteine.…”
Section: B Neurodegenerative Disordersmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed as described previously (Massie et al, 2008(Massie et al, , 2010. Primary antibodies comprised guinea pig antibody to VGLUT1 (1:2000; Millipore), mouse antibody to VGLUT2 (1:5000; Millipore), rabbit antibody to VGLUT3 (1:1000; Synaptic Systems), rabbit antibody to GLT-1 (1:30,000) (Yamada et al, 1998), rabbit antibody to glutamate-aspartate transporter (GLAST; 1:4000) (Shibata et al, 1997), rabbit antibody to EAAC1 (1:1000; Alpha Diagnostic), rabbit antibody to xCT (1:10,000) (Massie et al, 2008), mouse antibody to synaptophysine (1:5000; Stressgen), rabbit antibody to glyceraldehyde 3-phosphate dehydrogenase (GAPDH; 1:5000; Santa Cruz Biotechnology), and mouse antibody to GAPDH (1:15,000; Millipore).…”
Section: Western Blottingmentioning
confidence: 99%
“…System x c Ϫ exchanges intracellular glutamate for extracellular cystine, thereby supporting intracellular glutathione (GSH) synthesis as well as nonvesicular glutamate release (Bannai, 1986). Given this crucial dual role of system x c Ϫ , its potential involvement in neurodegenerative disorders has been investigated previously (Qin et al, 2006;Massie et al, 2008Massie et al, , 2011Lewerenz and Maher, 2009;Liu et al, 2009;Albrecht et al, 2010;Schallier et al, 2011). Nevertheless, system x c Ϫ was never studied in the context of hippocampus-dependent functions, e.g., spatial working memory or limbic seizure development.…”
Section: Introductionmentioning
confidence: 99%